Getting to the root of grafting-induced traits. (February 2021) - Williams, Brandon; Ahsan, Muhammad Umair; Frank, Margaret H
Abstract : Grafting is an ancient technique that involves the physical joining of genotypically distinct shoot and root systems, in order to achieve a desirable compound plant. This practice is widely used in modern agriculture to improve biotic and abiotic stress tolerance, modify plant architecture, induce precocious flowering and rejuvenate old perennial varieties, boost yield, and more. Beneficial new rootstock-scion combinations are currently identified through an inefficient trial and error process, which presents a significant bottleneck for the application of grafting to combat new environmental challenges. Identifying the mechanisms that underlie beneficial grafting-induced traits will facilitate rapid breeding and genetic engineering of new rootstock x scion combinations that exhibit superior performance across varying agricultural environments.